Ultrasonographic Measurement of Skin to Lumbar Epidural Space Depth in Pregnant Women Undergoing Elective Cesarean Section: An Observational Study - Sushila Lama Moktan; Milan Kumar Thapa; Ujma Shrestha; Prabin Subedi (Journal of Nepal Medical Association)
Introduction: Neuraxial anesthesia is commonly used during cesarean delivery and is preferred for its effectiveness and minimal risks. Accurate identification of the depth of the lumbar epidural space is crucial to ensure successful block and minimize complications. However, this can be challenging in pregnant women due to physiological changes that affect the anatomy of the lumbar spine. Ultrasound is a helpful device for providing real-time visualization of the relevant anatomical structures and facilitating accurate needle insertion. In this study, we evaluated the utility of ultrasound in determining the depth from the skin to the lumbar epidural space in pregnant women undergoing elective caesarean section. Methods: This is an observational cross-section study performed after approval from Institutional Review Committee (Reference number:09062023/03). Using a curvilinear ultrasound probe, imaging of spine at lumbar third and fourth intervertebral space was performed. The measurements were performed in the sitting position with the patients' backs flexed in the parasagittal oblique and transverse median view to determine the distance from the skin to the lumbar epidural space. Results: The mean depth from the skin to the lumbar epidural space/posterior complex in the parasagittal oblique view was 46.84±7.18 mm (95% CI: 45.48-48.20), and transverse median view was 45.27±8.16mm (95% CI: 43.73-46.81). Conclusions: The skin-to-lumbar epidural space depth in pregnant women undergoing elective cesarean section was comparable to other studies conducted in similar settings.